2017
DOI: 10.18805/lr-3798
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an isoflavone glycoside hydrolyzing b-glucosidase in the seeds of the desert legume Prosopis cineraria

Abstract: Legumes, in general, are rich in glycosidic isoflavone conjugates, whereby specific -glucosidases act to release the free aglycones that could serve in plant-microbe interactions and defense. Prosopis cineraria is an important legume tree, bearing medicinally useful and edible pods, generally growing in extreme arid/semi-arid zones of Rajasthan. However, specific phytochemical-cum-metabolic profiles are lacking for the same. Therefore, the present investigation undertook phytochemical and metabolic screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It has been reported that the desert legumes such as Prosopis cineraria and Cyamopsis tetragonoloba harbor thermostable β-glucosidase enzymes (EC 3.2.1.21), capable of showing significant catalytic activity even above 50°C temperature (V Asati & Sharma, 2018 ; Asati and Sharma, 2019 ). These enzymes were specific towards isoflavone glycosides and did not show any activity with glycosides of other flavonoid categories, possibly due to difference in structure of the substrate, that is, flavonoid parent skeleton (benzene ring connected to Carbon 3 of C-ring in case of isoflavonoids, as against Carbon 2 in case of flavonoids).…”
Section: Nature-inspired Biocatalysis Enzyme Engineering and Extremoz...mentioning
confidence: 99%
“…It has been reported that the desert legumes such as Prosopis cineraria and Cyamopsis tetragonoloba harbor thermostable β-glucosidase enzymes (EC 3.2.1.21), capable of showing significant catalytic activity even above 50°C temperature (V Asati & Sharma, 2018 ; Asati and Sharma, 2019 ). These enzymes were specific towards isoflavone glycosides and did not show any activity with glycosides of other flavonoid categories, possibly due to difference in structure of the substrate, that is, flavonoid parent skeleton (benzene ring connected to Carbon 3 of C-ring in case of isoflavonoids, as against Carbon 2 in case of flavonoids).…”
Section: Nature-inspired Biocatalysis Enzyme Engineering and Extremoz...mentioning
confidence: 99%
“…The commercial importance of food-based antioxidants is increasingly being realized, as exemplified by research on various plants including legumes, primarily due to the toxicity of synthetic antioxidants to humans [ 3 ]. Interestingly, many of these antioxidants such as flavonoids are stored in the plant cell's vacuole in glycosylated forms, which are acted upon by specific β-glucosidases to make the more active aglycone available to the plant [ 4 ]. On a more commercial forefront, Mai et al [ 5 ] have recently characterized a β-glucosidase from mangrove sediments, showing high catalytic activity on soy isoflavone glycosides.…”
Section: Introductionmentioning
confidence: 99%